Antibiotic Therapy for Children with Diarrhea in a Low-Resource Setting: A Syndromic Approach - Daga S; Daga A; Mhatre S (Dove Medical Press, 2020)
Subhashchandra Daga,1 Achla Daga,2 Sameer Mhatre1 1Department of Pediatrics, MIMER Medical College, Talegaon Dabhade 410507, India; 2Department of Community Medicine, Pacific Medical College, Udaipur 313001, IndiaCorrespondence: Subhashchandra DagaDepartment of Pediatrics, Pacific Medical College, Udaipur 313001, IndiaTel +91 9960522259Email dagasubhash49@gmail.comObjective: To compare age and protein-energy malnutrition (PEM) – the predispositions – and fever and abnormal leukocyte count (ALC) – the SIRS criteria – in hospitalized children with and without diarrhea.Design: A prospective case-control study.Setting: A pediatric ward of a general hospital in a low-resource setting.Participants: Totally, 445 consecutive admissions to the pediatric ward of a general hospital over a period of 1 year were included in this prospective case-control study; hemodynamically unstable subjects (11) were excluded.Interventions: Age, PEM, fever, and ALC were assessed in 59 patients with diarrhea and compared with 375 control patients without diarrhea. Odds ratios with confidence intervals were determined; the chi-square test and binary logistic regression analysis were also performed.Main Outcome Measures: Associations of diarrhea with age, PEM, fever and ALC singly and various combinations of predispositions and SIRS parameters.Results: Infancy and ALC were significantly associated with diarrhea. PEM or fever alone was not significantly associated with diarrhea; however, the probability of developing diarrhea was significantly higher when a combination of ALC and PEM was observed. The combination of infancy, PEM, and ALC carried a sensitivity of 81· 36%; for other combinations, sensitivity varied between 70% and 80%. The combination of infancy and ALC had the lowest sensitivity (59· 32%) but the best specificity (61· 07%).Conclusion: The association/presence of a combination of SIRS parameters (fever and ALC) and predispositions (infancy and PEM) in children with diarrhea may help in deciding whether antibiotic therapy should be initiated.Keywords: diarrhea in children, sepsis in children, SIRS in diarrhea, child mortality